2020
DOI: 10.3341/kjo.2019.0102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ocular Biometry and Refractive Outcomes Using IOL Master 500, IOL Master 700, and Lenstar LS900

Abstract: Satisfaction of patients undergoing cataract surgery is dependent on precise predictions of refractive outcomes. As accurate biometry and power precision of intraocular lens (IOL) have gained importance, development of various modern diagnostic techniques has enabled the control Purpose: To evaluate the agreement in ocular biometry outcomes measured by three different devices, the IOL Master 500, IOL Master 700, and Lenstar LS900, and compare the refractive outcomes after cataract surgery obtained using those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 19 publications
5
38
1
Order By: Relevance
“…In the Asian population, Song et al [4] show similar keratometry average value when using Lenstar and IOL Master 700 and a bit bigger when using IOL Master 500, while Wickremasinghe et al [18] show much close values to ours, using an autorefractor-keratometer (Canon RK-5 Autorefractor Keratometer; Canon, Inc., Tokyo, Japan). Cuban researchers [15,32] using autorefractor-keratometers have previously reported slightly lower values.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the Asian population, Song et al [4] show similar keratometry average value when using Lenstar and IOL Master 700 and a bit bigger when using IOL Master 500, while Wickremasinghe et al [18] show much close values to ours, using an autorefractor-keratometer (Canon RK-5 Autorefractor Keratometer; Canon, Inc., Tokyo, Japan). Cuban researchers [15,32] using autorefractor-keratometers have previously reported slightly lower values.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, this issue has to be considered when comparing Lenstar and IOL Master as Cuban researchers did in a previous study [ 27 ], showing values closer to ours, with no significant differences between these two biometers. In contrast, Song et al [ 4 ] observed that ACD measured by IOL Master 500 was shallower than that measured by IOL Master 700 or Lenstar LS900 (Haag Steit AG, Koeniz, Switzerland)). In Song's study, the ACD mean value is similar to ours when measured by IOL Master 500, while values from IOL Master 700 and Lenstar are deeper.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Refractive predictability was excellent in our study, with a mean postoperative residual SE of −0.17 D at 12 months and 95% of the eyes being within ±0.5 D of the target value. This suggests that advanced, swept source-based optical biometry 26 and modern IOL calculation formulae, such as the Barrett TK formula 27 , 28 used in the present study, may help cataract refractive surgeons to improve their chances of achieving postoperative targets closer to emmetropia in the majority of their cases.…”
Section: Discussionmentioning
confidence: 92%
“…The children were fully communicated with the examiner before the examination and natural blinking was permitted during the examination to avoid factors such as fixation differences and tear film rupture that could affect the results. The measurements were carried out by the same experienced technician ( 13 ). Three examinations were performed in each eye to assess the repeatability and reliability of the measured.…”
Section: Methodsmentioning
confidence: 99%